ANALISIS MEREK DAN STRATEGI PRODUK DALAM MEMBANGUN DAYA SAING PRODUK GULA SEMUT ORGANIK “SOLAREN” - Paendong, Melky K. E.; Kumaat, Arief Perdana; Adelaida Joroh; Kaparang, Gratia Natrina; Walangitan, Misael Aldo (Jurusan Administrasi Bisnis Politeknik Negeri Manado, 2026)
This article examines branding strategy and product strategy as instruments to build the competitiveness of “SOLAREN”, an organic palm sugar granule (gula semut) product manufactured through an integrated photovoltaic (PV) powered production system in Talaitad Utara Village, South Minahasa. The national palm sugar market continues to grow while domestic production still fails to meet roughly thirty percent of demand, and export potential through HS Code 170290 keeps expanding, opening opportunities for villagebased producer groups to enter premium and export segments. This study employs a descriptive qualitative approach using secondary data derived from a marketing review report, examining market analysis, competitor benchmarking, brand architecture, digital marketing channels, and food safety and quality certification. The findings show that SOLAREN's brand strategy, which combines clean solar-based technology with the authenticity of local sap, together with a structured product differentiation strategy covering consistent moisture content, uniform colour, fine texture, and staged certification, is able to position SOLAREN as a premium product capable of competing with manually produced palm sugar as well as established national brands. Integrated branding and product strategy supported by digital marketing channels and renewable energy technology are concluded to be key determinants in strengthening the competitiveness of village-basedorganic palm sugar products.